Knowledge-based environments in the city: design and urban form in the Helsinki metropolitan area. (19th July 2019) - Ponto, Heli; Inkinen, Tommi
Knowledge-based development (KBD) is of interest to cities, as it promotes economic growth and boosts dynamic urban image. Creative environments are arguably highly dependent on sociality, and they are usually located near city centres. The focus of this study is on three knowledge-based locations in the Helsinki metropolitan area (HMA) in Finland. The research material composes of field observation data and photographs. Results indicate that knowledge-intensive environments include several elements of good city design, for example, pedestrian-friendly street networks and green areas, but they tended to lack vibrant urban life, that is, human activity. The findings support the claim that information and communication technology (ICT)-based companies are not very dependent on the sociality of environment. As cities are spaces for individuals working, studying and visiting, attention must be paid to the urban design of these areas.